2015
DOI: 10.1002/jrs.4603
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of poly(lactic acid)/poly(methyl methacrylate) blend tablets for application in quantitative analysis by micro Raman spectroscopy

Abstract: Poly(lactic acid) (PLA) is a biodegradable polymer that has a variety of applications, one of which is as biomaterial in surgery or as functional layers on implants, due to its compatibility with living tissue. This paper reports the possibilities of quantification of poly(lactic acid) (PLA) in a polymer matrix such as poly(methyl methacrylate) (PMMA) by micro Raman spectroscopy (MRS). Blends of amorphous poly(DL‐lactic acid) with poly(methyl methacrylate) were prepared by the procedure of dissolution/precipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…[36][37][38][39][40][41][42] Recently, PMMA has received great interest as a blend candidate for PLA due to its higher glass transition temperature and complementary mechanical properties. 38,[43][44][45][46][47][48][49][50][51][52][53][54] However, conclusions regarding the miscibility of PLA/PMMA blends are somewhat contradictory in the literature. Samuel et al report that blends prepared by solvent casting are immiscible.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39][40][41][42] Recently, PMMA has received great interest as a blend candidate for PLA due to its higher glass transition temperature and complementary mechanical properties. 38,[43][44][45][46][47][48][49][50][51][52][53][54] However, conclusions regarding the miscibility of PLA/PMMA blends are somewhat contradictory in the literature. Samuel et al report that blends prepared by solvent casting are immiscible.…”
Section: Introductionmentioning
confidence: 99%
“…Figure illustrates the Raman spectra for both PLLA/PMMA‐only and PLLA/PMMA with GFP‐HABP fibers incubated either in biomineralization buffer only (vehicle control) or biomineralization buffer with the addition of AP enzyme to catalyze mineral formation. The peaks at 812 cm −1 are associated with COC symmetric stretching of the PLLA/PMMA polymer blend . The bands at 960 cm −1 are characteristic of PO symmetric stretching in phosphate groups, as noted in hydroxyapatite mineral .…”
Section: Resultsmentioning
confidence: 88%
“…The peaks at 812 cm −1 are associated with COC symmetric stretching of the PLLA/PMMA polymer blend. [29] The bands at 960 cm −1 are characteristic of PO symmetric stretching in phosphate groups, as noted in hydroxyapatite mineral. [28] For each mineralized fiber sample, a ratio was taken of the 960 and 812 cm −1 bands to measure differences in the degree of mineralization.…”
Section: Biomineralizationmentioning
confidence: 99%
“…PLA is a biodegradable polymer that has a variety of applications, one of which is as biomaterial in surgery or as functional layers on implants, due to its compatibility with living tissue. This study demonstrated that Raman spectroscopy provides an alternative non‐destructive method for quantitative analy of PLA in a PMMA matrix …”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…This study demonstrated that Raman spectroscopy provides an alternative non-destructive method for quantitative analy of PLA in a PMMA matrix. [129] Glasses, ceramics, powders and disordered materials Di Genova and co-workers described an approximate chemical analysis of volcanic glasses using Raman spectroscopy. They anticipate its application in handheld in situ terrestrial field studies of silicate glasses under extreme conditions, such as extraterrestrial and submarine environments.…”
Section: Single Crystalsmentioning
confidence: 99%